Analisis Model Matematika Dasar Dalam Strategi Pengelolaan Hama Tanaman - Mendrofa, Elsa Greta; Munika, Tari (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Pest management is one of the greatest challenges in agriculture, affecting crop yield and quality. To optimize pest control, the application of basic mathematical models can provide a more efficient, systematic approach to planning control strategies. This paper analyzes various basic mathematical models used in pest management, including models for pest population prediction and the dynamics of pest-plant interactions. Additionally, the study discusses the application of these models in designing control policies that minimize pest-related losses while considering environmental, economic, and technical factors. The results of the analysis show that the application of mathematical models can enhance pest management efficiency by providing data-driven guidance in determining the appropriate timing and type of intervention. This research aims to contribute to the development of more sustainable and evidence-based pest management strategies.